Density, race, and vote choice in the 2008 and 2012 presidential elections - Jeremy M. Teigen (Research & Politics, 2017)
Voting is a complex dynamic driven by the sociopolitical attributes of individuals and how they are spatially located in proximity to similar or different populations. In this research note we examine how presidential vote choice is influenced by the interaction between the population density and racial composition of the ZIP code of respondents in the 2008 and 2012 Cooperative Congressional Election Studies. Our findings reveal interesting patterns with respect to a respondent’s racial background. For whites in racially diverse settings, as density increases, so does support for Obama. By contrast, for blacks the spatial and racial context has almost no effect, providing evidence in support of the claim that this is a group strongly attached to the Democratic Party and its co-racial standard-bearer.